Evaluation of the Antileishmanial Activity of Some Benzimidazole Derivatives Using In Vitro and In Silico Techniques - Mustafa Eser; İbrahim Çavuş; Aybüke Züleyha Kaya; Asaf Evrim Evren; Leyla Yurttaş (Veterinary Sciences, 2025)
Benzimidazole derivatives are well known for their anthelmintic activity. Investigating the potential efficacy of new derivatives of this class against various parasites is essential to identify novel drug candidates. For this purpose, an in-house molecular database was screened, and four benzimidazole-based molecules were chosen to evaluate antiprotozoal activity. The compounds (K1–K4) had been previously synthesized through a four-step procedure. The potential in vitro cytotoxic properties of the compounds were assessed against the Leishmania (L.) major strain and L929 mouse fibroblast cells. The tests indicated that K1 (3-Cl phenyl) demonstrated an antileishmanial effect (IC50 = 0.6787 µg/mL) and cytotoxicity at elevated concentrations (CC50 = 250 µg/mL) in healthy cells. These findings were comparable to those of AmpB. The antileishmanial activity values were determined as follows: K2; 8.89 µg/mL, K3; 45.11 µg/mL, K4; and 69.19 µg/mL. The CC50 values were determined as follows: K2, 63 µg/mL; K3; 0.56 µg/mL; and K4, 292 µg/mL. Molecular docking and dynamic simulations were conducted to elucidate the potential mechanisms of action of the test substances. In silico investigations indicated interactions between the compounds and the active site of pteridine reductase 1 (PTR1), which is a biosynthetic enzyme essential for parasite proliferation. N-alkyl benzimidazole-based compounds exhibit potential inhibitory activity against L. (L.) major promastigotes. Therefore, these findings suggest that in vivo evaluation is warranted, and structural modifications may lead to the identification of more effective antileishmanial agents.